Hubungan Pola Asuh Ibu Dengan Kejadian Stunting Pada Balita Di Desa Manarap Kecamatan Danau Panggang - Dewi Susanti (LPPM Sekolah Tinggi Ilmu Pertanian Amuntai, 2024)
Stunting is closely related to poor parenting practices, parenting patterns allow stunting to occur in children if parents do not provide additional nutrition other than ASI. The aim of the research is to analyze the relationship between maternal parenting patterns in feeding and the incidence of stunting among toddlers in Manarap Village, Danau Panggang District, North Hulu Sungai Regency. The research was carried out in Manarap Village, Danau Panggang District, North Hulu Sungai Regency. Research time starts from November 2023 to February 2024. The research was conducted in Danau Panggang District because this area is an area vulnerable to food problems based on food utilization analysis. The use of univariate and bivariate analysis was used to support data analysis in this study. he results of the research showed that of the children under five who received inappropriate parenting patterns in feeding, 10 toddlers experienced stunting while 3 toddlers did not experience stunting. On the other hand, of the toddlers who received proper maternal care in feeding, 5 toddlers experienced stunting and 12 toddlers did not experience stunting. There is a significant correlation between maternal parenting patterns in providing food and the incidence of stunting in toddlers in Manarap Village, Danau Panggang District, North Hulu Sungai Regency, based on the results of the Chi-Square statistical test with Asymp values. Sig (2-sided) = 0.027 and p value < α = 0.05.